1999
DOI: 10.1111/j.1471-0528.1999.tb08269.x
|View full text |Cite
|
Sign up to set email alerts
|

Anal incontinence after vaginal delivery: a prospective study in primiparous women

Abstract: Objective To investigate the incidence and degree of anal incontinence after vaginal delivery among Design Prospective observational study.Setting Karolinska Institutet, Danderyd Hospital, Sweden, a university hospital.Participants Three hundred and forty-nine primiparous women.Methods Questionnaires distributed within the first days after delivery and re-distributed five and nine months postpartum. Analysis of delivery records.Results Eighty percent of the women answered all questionnaires. At five months pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
72
9
6

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(99 citation statements)
references
References 29 publications
(3 reference statements)
12
72
9
6
Order By: Relevance
“…A study has shown that increasing maternal age as a risk factor for developing anal incontinence after delivery [13]. But our study demonstrated an opposite finding to this.…”
Section: Discussioncontrasting
confidence: 57%
“…A study has shown that increasing maternal age as a risk factor for developing anal incontinence after delivery [13]. But our study demonstrated an opposite finding to this.…”
Section: Discussioncontrasting
confidence: 57%
“…The Hunskaar score 13 described UI severity as the product of the frequency and volume of incontinent episodes (range 0-12). Severity categories are: continent (0), slight (1-2), moderate (3-6), severe (7)(8)(9), and very severe (10)(11)(12).…”
Section: Methodsmentioning
confidence: 99%
“…2,3,7 The Pelvic Floor Disorders Network (PFDN) has previously published findings of the Childbirth and Pelvic Symptoms (CAPS) study, 8 which examined the prevalence of FI and UI in 3 cohorts of primiparous women. FI was more prevalent (17.0%) in women who delivered vaginally with recognized anal sphincter tears, compared with women who delivered Reprints not available from the authors.…”
Section: Abstract Childbirth; Fecal Incontinence; Quality Of Life; Urmentioning
confidence: 99%
“…Outros autores estudaram as repercussões de longo prazo relacionadas ao tipo de parto. Descreve-se maior incidência de perda urinária de esforço 33 e incontinência fecal 34 associadas ao parto vaginal, especialmente com o vaginal operatório, e maior risco de placenta prévia, descolamento prematuro de placenta 35 e rotura uterina 36 em gestações subseqüentes associados à cesárea. Thompson et al 37 organizaram uma coorte que acompanhou mulheres 8, 16 e 24 semanas após o parto e avaliou, por meio de questionário respondido pelas mulheres, a freqüência de sintomas subjetivos e reinternação.…”
Section: Introductionunclassified